"Against all odds": Head chefs profiled. Issue 2 (2nd April 2016) - Allen, Hannah; Mac Con Iomaire, Máirtín
ABSTRACT: This study based on a survey of 170 head chefs provides the first comprehensive empirical data on the profile of head chefs in the Republic of Ireland. Eighty-four percent of head chefs were male and the majority (48.8%) were in their thirties. There is an increased rise in the attainment of degrees (currently at 35%), but findings showed that it takes years to advance in the industry, where there is a high rate of turnover. This article both reviews and adds to the international literature on the occupation of chef and raises questions for further research such as: Why are there so few female head chefs in Ireland? What is the best way to manage talent and improve retention of head chefs? Why are there more migrant head chefs working in restaurants rather than hotels? Findings from this may benefit industry stakeholders, employers, educators, and prospective culinary students.